Pharmaceutics - Fox, Shelley Chambers (Pharmaceutical Press, 2014)
Remington Education: Pharmaceutics covers the basic principles of pharmaceutics, from dosage forms to drug delivery and targeting. It addresses all the principles covered in an introductory pharmacy course. As well as offering a summary of key information in pharmaceutics, it offers numerous case studies and MCQs for self assessment.